Carbon emissions management control systems: Field study evidence. (10th November 2017) - Bui, Binh; de Villiers, Charl
Abstract: The paper examines the types and role of carbon management control systems by analysing in-depth interviews undertaken with 38 individuals from 30 organizations that use carbon management control systems. The paper identifies the different types of carbon controls, and the internal and external uses and objectives of controls. Carbon controls can be used to achieve compliance or improve performance, and organizations can focus on different objectives at different times. The findings suggest that emissions reductions do not occur without absolute (as opposed to intensity) reduction targets, management support, and resource allocation for carbon management. The findings further suggest that firms that want to improve performance or manage compliance costs effectively will require the integration of carbon controls into operational and strategic processes. A framework is developed that managers and researchers can use as an implementation guide or a research framework. The framework highlights three elements that were found to be critical to ensure control effectiveness, namely managerial communication, quality of information, and employee perceptions. The evidence suggests that communication of carbon information through appropriate channels and language, as well as high quality of carbon information are essential to ensure positive employee perceptions and buy-in, which will contribute to effective carbon reduction.